Optimum geometry and performance of a dual-mode horn modification. - Skobelev, Sergei P. (IEEE Antennas & propagation magazine.)
We have carried out the optimization of the simplest dual-mode horn that does not include the special cylindrical phasing section. Calculation of the horn characteristics has been performed by using a stepped representation of the conical section, with a subsequent application of the method of generalized scattering matrices, which more accurately accounts for all of the effects taking place when exciting the horn, The objective of the optimization has been the minimization of the maximum crosspolar level. The optimum horn parameters obtained as a result, and the corresponding radiation characteristics, can serve as additional reference information in the development of antenna systems using dual-mode horns.